2003
DOI: 10.4049/jimmunol.171.12.6349
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Naive CD8 T Cells Requires Persistent Antigen and Is Not Programmed by an Initial Signal from the Tolerogenic APC

Abstract: Activation of naive CD8 T cells in vivo requires the recognition of cognate peptide-MHC complexes on APCs. Depending upon the activation status of the APC, such recognition will promote either a vigorous immune response or T cell tolerance and deletion. Recent studies suggest that the initial signals provided by APCs are sufficient to program the proliferation of naive CD8 T cells and their differentiation into effector cells. In this study, we sought to determine whether an initial encounter with tolerogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…Surprisingly, we found that a significant number of cells could survive following their initial exposure to Ag and that activation with quiescent APCs did not result in complete deletion (9). These data suggested that during tolerance induction, deletion of naive CD8 T cells was not programmed during the initial stimulatory event and that additional exposure to Ag was required to achieve complete clonal deletion.…”
mentioning
confidence: 56%
“…Surprisingly, we found that a significant number of cells could survive following their initial exposure to Ag and that activation with quiescent APCs did not result in complete deletion (9). These data suggested that during tolerance induction, deletion of naive CD8 T cells was not programmed during the initial stimulatory event and that additional exposure to Ag was required to achieve complete clonal deletion.…”
mentioning
confidence: 56%
“…In contrast, naive clone 4 T cells do not spontaneously acquire effector functions or induce diabetes following their adoptive transfer into InsHA mice (Fig. 2D and Table I) (8,41). This has allowed us to observe an effect of Bcl-2 over-expression in promoting acquisition of effector function.…”
Section: Discussionmentioning
confidence: 79%
“…These data support previous studies stating peripheral tolerance induction requires continual antigen stimulation. 24,25 However, the previous studies could not assess the activation status of responding cells without amplification and they relied on in vitro selection and adoptive transfer to assess the necessity for continued antigen expression. The POET-I model provided an unique opportunity to assess reactive cells within the host through castration and the resulting loss of high level antigen expression.…”
Section: Discussionmentioning
confidence: 99%